The effect of Nigella sativa on infertility in men and women: a systematic review - Darand, Mina; Mirmiran, Parvin; Mokari-Yamchi, Amin; Mokari-Yamchi, Amin (Progress in Nutrition, 2020)
Bobjective: Black seed (Nigella sativa L.) is a medicinal plant belonging to botanical family of Ranunculaceae. Given the effective role of N. sativa in treating different diseases, the present systematic review aimed to evaluate the effects of N. sativa on the reproductive system. Materials and Methods: The current systematic review was carried out on randomized controlled trials (RCTs) regarding human, animal and in vivo/in vitro studies published between 2014 and 2017. The related articles were collected by searching the databases of Medline, PubMed, Scopus, Science direct, and Google scholar only in English using the search keywords of Nigella sativa, Black Seed, Thymoquinone (TQ), Infertility, Reproductive System and Reproductive Parameters. Review articles, case reports, abstract in symposium and congress were excluded. Results: Finally, 24 articles were selected for analyses. The results showed that the treatment with N. sativa has improved the sperm parameters, semen fluid in men and leydig cell count, graph follicle count, corpus luteum and level of sex hormones such as testosterone and progesterone in women (p